PENGARUH MODAL DAN TENAGA KERJA USAHA PENGRAJIN BATIK TULIS KLASIK TERHADAP TINGKAT PRODUKSI (Studi Pada Industri Kecil Menengah “ IKM “ Batik Tulis Klasik di Desa Margorejo, Kecamatan Kerek, Kabupaten Tuban) - Muhammad Nur Hidayatullah (Jurnal Ekonomi Pembangunan, 2013)
The objective of this study was to investigate the effects of capital and labor in both small and medium industries of classic batik entrepreneurs in Margorejo Village, Kerek District, Tuban. The result of multiple linear regression analysis shows that: Y = -6.286474 + 0.695922 1.260502 X1 + X2. Regression coefficient of 0921 states the influence of the amount of labor (X1) and capital (X2) on the production of batik per month (Y), meaning amount of labor (X1) and capital (X2). While the rest of 7.80% is determinaned by factors beyond the studied variables